2021
DOI: 10.3390/agronomy11040641
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Green Waste Compost and Biomass Combustion Ash for Recycled Nutrient Delivery to Soil

Abstract: The use of major nutrient-containing solid residuals, such as recycled solid waste materials, has a strong potential in closing the broken nutrient cycles. In this work, biofuel ash (BA) combined with green waste compost (GWC) was used as a nutrient source to improve soil properties and enhance wheat and triticale yields. The main goal was to obtain the nutrient and heavy metal release dynamics and ascertain whether GWC together with BA can potentially be used for concurrent bioremediation to mitigate any nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Even though Cu and Zn could be either micronutrients or heavy metals depending on the concentration range, the excess of these elements in the soil negatively affects plants' growth and development [50]. Previously performed studies confirm the findings that various by-products (compost, sewage sludge, bio ash, and wastewater) from Lithuania show higher contaminations levels for Cu and Zn than for other metals [28,[51][52][53]. Other authors who used white mustard for heavy metals phytoextraction demonstrated that Cu and Zn accumulation was lower than radish, perennial rye, and green pea [54].…”
Section: Resultsmentioning
confidence: 79%
“…Even though Cu and Zn could be either micronutrients or heavy metals depending on the concentration range, the excess of these elements in the soil negatively affects plants' growth and development [50]. Previously performed studies confirm the findings that various by-products (compost, sewage sludge, bio ash, and wastewater) from Lithuania show higher contaminations levels for Cu and Zn than for other metals [28,[51][52][53]. Other authors who used white mustard for heavy metals phytoextraction demonstrated that Cu and Zn accumulation was lower than radish, perennial rye, and green pea [54].…”
Section: Resultsmentioning
confidence: 79%
“…Most organic compounds like amino acids, proteins, nucleic acids, and compounds of secondary plant metabolism have N as their important make-up [ 15 , 39 ], making it a pathway for crop productivity and yield. The efficiency of N uptake and use relative to the production of grain requires that the processes associated with absorption, translocation, assimilation, and redistribution of N operate effectively [ 34 , 40 ]. The addition of N into the soil caused the retention of N in the upper soil profile, which invariably increased the NUE arising from greater N uptake and resulting in less or decreased N in soil after harvest.…”
Section: Resultsmentioning
confidence: 99%
“…For chemical analysis, soil samples were collected before the first-year cultivation and after the third-year harvest (after 29 months) from the start of the experiment. The determination of soil acidity (pH) was made in a 1:5 (vol −1 ) soil suspension in the 1M KCl solution [ 40 ]. Soil mobile potassium (K 2 O), mobile phosphorus (P 2 O 5 ), mobile calcium (Ca), and mobile magnesium (Mg) were determined using an ammonium lactate–acetic acid extraction, as described by Egner, Riehm, and Domingo [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation